Diaspora’s Dharma: Buddhist Connections across the South China Sea,1900–1949 - Chia, Jack Meng-Tat (Contemporary buddhism, 2020)
The restoration of Nanputuo Monastery (Nanputuo si 南普陀寺) in Xiamen and the revival of its South China Sea Buddhist networks in recent decades are significant factors in the religious resurgence in southeast China since the reform and open-door period. This article looks at an earlier role of such networks in this region, using Nanputuo Monastery as a case study, to explore the transregional Buddhist connections between southeast China and the Chinese diaspora from the turn of the twentieth century to 1949. It argues that new patterns of Buddhist mobility contributed to the circulation of people, ideas, and resources across the South China Sea. I show that, on the one hand, Buddhist monks and religious knowledge moved along these networks from China to Southeast Asia, while money from wealthy overseas Chinese was channelled along the networks for temple building in China; on the other hand, Buddhist monks relied on the networks to support China’s war effort and facilitate their relocation to Southeast Asia during the Sino-Japanese War. Examining these networks also explains the emergence of modernist Chinese Buddhism throughout Southeast Asia in the early to mid-twentieth century.